The “Lipid Accumulation Product” Is Associated with 2-Hour Postload Glucose Outcomes in Overweight/Obese Subjects with Nondiabetic Fasting Glucose - Alexis Elias Malavazos; Emanuele Cereda; Federica Ermetici; Riccardo Caccialanza; Silvia Briganti; Mariangela Rondanelli; Lelio Morricone (International Journal of Endocrinology)
“Lipid accumulation product” (LAP) is a continuous variable based on waist circumference and triglyceride concentration previously associated with insulin resistance. We investigated the accuracy of LAP in identifying oral glucose tolerance test (OGTT) abnormalities and compared it to the homeostasis model assessment of insulin resistance (HOMA-IR) in a population of overweight/obese outpatients presenting with nondiabetic fasting glucose. We studied 381 (male: 23%) adult (age: 18–70 years) overweight/obese Caucasians (body mass index: 36.9 ± 5.4 Kg/m2) having fasting plasma glucose < 7.0 mmol/L. OGTT was used to diagnose unknown glucose tolerance abnormalities: impaired glucose tolerance (IGT) and type-2 diabetes mellitus (T2-DM). According to OGTT 92, subjects had an IGT and 33 were diagnosed T2-DM. Logistic regression analysis detected a significant association for both LAP and HOMA-IR with single (IGT and T2-DM) and composite (IGT + T2-DM) abnormal glucose tolerance conditions. However, while the association with diabetes was similar between LAP and HOMA-IR, the relationship with IGT and composite outcomes by models including LAP was significantly superior to those including HOMA-IR (P=0.006 and P=0.007, resp.). LAP seems to be an accurate index, performing better than HOMA-IR, for identifying 2-hour postload OGTT outcomes in overweight/obese patients with nondiabetic fasting glucose.